Increased expression of protein kinase A inhibitor α (PKI-α ) and decreased PKA-regulated genes in chronic intermittent alcohol exposure. - Repunte-Canonigo, Vez (Brain Res, 2007)
Intermittent models of alcohol exposure that mimic human patterns of alcohol consumption produce profound physiological and biochemical changes and induce rapid increases in alcohol self-administration. We used high-density oligonucleotide microarrays to investigate gene expression changes during chronic intermittent alcohol exposure in three brain regions that receive mesocorticolimbic dopaminergic projections and that are believed to be involved in alcohol’s reinforcing actions: the medial prefrontal cortex, the nucleus accumbens and the amygdala. An independent replication of the experiment was used for RT-PCR validation of the microarray results. The protein kinase A inhibitor α (PKI-α, Pkia), a member of the endogenous PKI family implicated in reducing nuclear PKA activity, was found to be increased in all three regions tested. Conversely, we observed a down-regulation of the expression of several PKA-regulated transcripts in one or more of the brain regions studied, including the activity and neurotransmitter-regulated early gene (Ania) -1, -3, -7, -8, the transcription factors Egr1 and NGFI-B (Nr4a1) and the neuropeptide NPY. Reduced expression of PKA-regulated genes in mesocorticolimbic projection areas may have motivational significance in the rapid increase in alcohol self-administration induced by intermittent alcohol exposure